2010
DOI: 10.1017/s1751731109991157
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of (co)variance components and genetic parameters for body weights and first greasy fleece weight in Bharat Merino sheep

Abstract: (Co)variance components and genetic parameters of weight at birth (BWT), weaning (3WT), 6, 9 and 12 months of age (6WT, 9WT and 12WT, respectively) and first greasy fleece weight (GFW) of Bharat Merino sheep, maintained at Central Sheep and Wool Research Institute, Avikanagar, Rajasthan, India, were estimated by restricted maximum likelihood, fitting six animal models with various combinations of direct and maternal effects. Data were collected over a period of 10 years (1998 to 2007). A log-likelihood ratio t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
16
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 24 publications
19
16
8
Order By: Relevance
“…The phenotypic variance found herein was superior to those reported by Gowane et al (2010), for Bharat Merino sheep (0.347). Nevertheless, they obtained a residual variance of 0.260, with consequent estimates of direct additive and maternal permanent environmental variances of 0.017 and 0.067, respectively.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…The phenotypic variance found herein was superior to those reported by Gowane et al (2010), for Bharat Merino sheep (0.347). Nevertheless, they obtained a residual variance of 0.260, with consequent estimates of direct additive and maternal permanent environmental variances of 0.017 and 0.067, respectively.…”
Section: Resultscontrasting
confidence: 76%
“…However, the one that best fit the data by the AIC and, consequently, was selected to present the genetic components was model 3. Gowane, Chopra, Prince, Paswan and Arora (2010), who found the best fit to the data for the model that considered direct additive and maternal permanent environmental effects. Gowane et al (2010) reported that several studies failed to partition the maternal additive and maternal environmental effects due to the requirement of repeated records for the sheep and, consequently, larger data volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maternal heritability (m 2 ) for different body weight traits showed a decreasing trend with the advance of age. Gowane et al (2010) also reported that the maternal genetic effects expressed during gestation and lactation are expected to have a diminishing influence on weight as the kits grow. Higher importance of maternal effect over additive genetic effect on the post weaning growth traits in rabbits had been reported earlier (Ferraz et al, 1992;Lukefahr et al, 1993).…”
Section: Body Weight Traitsmentioning
confidence: 99%
“…Small ruminants play a major role for strengthening the backbone of rural economy; especially sheep are integral to the cultural, social and economic livelihood of the rural farmers [1]. The profitability of a sheep production system is determined by both fertility and production traits [2].…”
Section: Introductionmentioning
confidence: 99%